2022
DOI: 10.1111/ijfs.15687
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of using possibility of grape pomace in wafer sheet for wheat flour substitution

Abstract: In this study, grape pomace (GP), a by-product consisting of grape skins and seeds rich in dietary fibres and polyphenols, was used in wafer sheets at different concentrations [5.00 (GP5), 10.0 (GP10), and 15.0 g 100 g À1 (GP15)] for the partial replacement of wheat flour (WF) and improve the functionality of wafer sheets. The GP inclusion at concentrations higher than 5.00 g 100 g À1 significantly affected the texture of sheets as well as the flow behaviour of batters, resulting in softer sheets and more visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Therefore, it may not have completely dissolved in the water base of the juice (Foschia et al, 2013;Slavin et al, 2009) and resulted in lower liking scores for appearance and texture since GP particles were visible. GP's particle size could also contribute to consumers' perception of its sensory attributes during consumption (Altinok et al, 2022). Torri et al (2015) found that particle size influenced flavor perception in dietary fiber and polyphenol-enriched tomato purees that contained added winery byproducts, but the particle size was not evaluated in this study.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, it may not have completely dissolved in the water base of the juice (Foschia et al, 2013;Slavin et al, 2009) and resulted in lower liking scores for appearance and texture since GP particles were visible. GP's particle size could also contribute to consumers' perception of its sensory attributes during consumption (Altinok et al, 2022). Torri et al (2015) found that particle size influenced flavor perception in dietary fiber and polyphenol-enriched tomato purees that contained added winery byproducts, but the particle size was not evaluated in this study.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, it may not have completely dissolved in the water base of the juice (Foschia et al., 2013; Slavin et al., 2009) and resulted in lower liking scores for appearance and texture since GP particles were visible. GP's particle size could also contribute to consumers' perception of its sensory attributes during consumption (Altinok et al., 2022). Torri et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results of texture attributes were in line with the TPA analysis, according to which WB5% and SB5% had higher hardness than the control samples. The use of saffron floral by-products made breads softer than the control samples, reducing their crispness and affecting their cohesiveness, probably due to the addition of this vegetal ingredient that interrupts the gluten network, making breads more fragile [ 33 ]. However, with respect to adhesiveness to palate and stickiness to teeth, no important differences were observed between the studied bread formulations.…”
Section: Resultsmentioning
confidence: 99%
“…The force‐time data were recorded, and then hardness (N) was determined from the maximum peak force and fracturability (mm) was determined from the distance at which the samples were broken. In the analysis, at least six tests were used to calculate the mean values for the hardness (N) and fracturability (mm) parameters of the chocolate‐enrobed wafer samples (Altinok et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%